Training on Calculation of Cost of Cost of Homemade Yoghurt Production for Mothers Citizens of Labuh Baru Barat Village - Wahyuni, Sri; Ramadhani, Suci; Adriyani, Annesa; Prihastuti, Asepma Hygi; Zainal, Rahmi (Doctoral Program of Social Science, Pasundan University, 2024)
Community service activities carried out by a team of accounting lecturers with partners from one of the culinary MSMEs that make and sell yoghurt drinks in the Labuh Baru Barat sub-district, Pekanbaru City. The number of MSME participants is 15 members. This MSME is a family business whose production process is carried out by women residents of West Labuh Baru Village, Pekanbaru City. This yogurt making business has been going on since 2020, and has been marketed to several local residents through consignment sales to several shops and supermarkets in Pekanbaru City. The problem faced by partners is weakness in determining product selling prices. The results of the Pre Test and Post Test are: 1) Respondents' responses regarding the understanding of raw material costs, 3 participants answered correctly in the Pre Test and 12 participants answered incorrectly, 15 people answered correctly in the Post Test; 2) Respondents' responses regarding the labor cost component, Pre Test answers, none of the participants answered the question correctly, Post Test answers all answered correctly; 3) Respondents' responses regarding the meaning of factory overhead costs, only 1 participant answered the Pre Test correctly, all the Pre Test answers answered correctly; 4) Respondents' responses regarding the method for calculating the cost of goods sold, there were no correct answers, all Post Test answers were correct.